KESETARAAN GENDER DAN INKLUSI SOSIAL SEBAGAI MISI SEKOLAH DI ERA SOCIETY 5.0 - Amalia Fitri,; Mohammad Havis,; Rayatul Akbar,; Vira Adzkia,; Pringgandani Al Asri,; Novita Wulandari,; Niken Cahya Rani,; Tia Amelia Adha,; Vanesha Chintami Putri, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
In the face of technological and societal transformations, new challenges emerge in the form of gender disparities and the imperative of inclusion. Schools have become a pivotal pillar in ensuring the realization of these missions within education. Era Society 5.0, a fusion of technology and society, presents collaborative opportunities. However, challenges related to inclusion and gender equality persist. Schools play a vital role in addressing gender disparities and fostering an inclusive environment, as underscored through the curriculum and daily interactions. The implementation of gender equality and social inclusion is executed through socialization, lectures, and the utilization of instructional media. The socialization efforts at SMPN 5 Kampar Kiri Hilir were successful and highlight the indispensable role of schools in driving positive social change. The significance of schools as primary drivers in shaping a generation that comprehends and applies gender equality and social inclusion in daily life is emphasized. Schools assume a central role in steering society towards positive change in Era Society 5.0